Optimization Calculation Method of Injection Voltage and Series Converter Capacity for Unified Power Flow Controller - Junwei LIU; Zhanhong LIANG; Zhanzhi LIU; Jiefeng ZHONG; Zifan ZHANG (南方能源建设, 2023)
[Introduction] The application of UPFC (Unified Power Flow Controller) is to increase the transmission capacity of key sections, which mainly through the injection of a certain series voltage into the system and therefore divert the power flow of target line. [Method] Focusing on the key transmission sections, the regional power grid was divided into the transmission network, the interconnection network and the internal network based on their function, then the Gaussian elimination method was used to equalize the system network into a two-channel constant power exchange system. On this basis, based on the energy conservation principle, the phasor method was applied to provide phasor graph of the voltage, power angle, impedance, and active power relationship between the UPFC branch and the equivalent branch before and after the UPFC was put into operation, respectively, for the stand-alone infinity system and the constant power exchange system. The classical power transfer function was used to deduced the UPFC injection voltage and series converter capacity calculation formula. [Result] The calculation method is simple and practical, especially suitable for power system planning and design stage. [Conclusion] The above method is applied to the calculation of Shenzhen power grid example, and compared with the simulation results of PSCAD, the validity and practicability of the method are verified.